A teenager's guide to life and love - Spock, Benjamin, 1903- (New York : Simon and Schuster, 1970)
Discusses various aspects of sexual behavior and the problems encountered by young people in sexual, emotional and social involvements.
Keywords: Sex instruction for youth; Youth -- Conduct of life; Sex instruction for youth; Youth -- Conduct of life